Studying research collaboration via co-authorship analysis in the field of TeL: The case of Educational Technology & Society Journal - Zervas, P.; Tsitmidelli, A.; Sampson, Demetrios; Chen, N.; Kinshuk (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 IEEE. In this paper, we analyze the co-authorship network of researchers who have published their joint work in Educational Technology & Society (ETS) Journal. The results of our analysis provided us with evidence that the ETS Journal co-authorship network is highly fragmented with a large number of non-connected subgroups of authors. Additionally, authors and collaborations of the ETS network have been polynomially increasing during the past 15 years.